Exploring the Impact of Artificial Intelligence on Student Creativity in Vietnamese Tertiary EFL Classrooms: Teacher Perspectives - Pham, Trut Thuy; Le, Thanh Thao (Universitas Veteran Bangun Nusantara, 2024)
This qualitative study investigates the perceptions of Vietnamese tertiary English as a Foreign Language (EFL) teachers regarding the impact of artificial intelligence (AI) on student creativity in language learning. Amidst the rapid integration of AI in educational contexts, this research focuses on a relatively unexplored area: the intersection of AI technology and creative language pedagogy in the Vietnamese educational setting. Nine EFL teachers from two institutions in Vietnam, representing novice, mid-career, and near-end career stages, participated in semi-structured interviews. The study employed the Technology Acceptance Model (TAM) and the Creativity in Language Learning Framework (CLLF) as its theoretical basis. Thematic analysis of the interview data revealed four key themes: the perceived impact of AI on creative language practice, challenges in integrating AI with creative pedagogy, varied perceptions of AI’s role in developing student autonomy, and the impact of AI on traditional teaching methods and teacher roles. The findings indicated a spectrum of perspectives, from viewing AI as a beneficial tool for creative engagement to concerns over its potential to limit creative thinking and traditional pedagogical approaches. The study highlights the complexity of integrating AI into language learning and its influence on both teaching practices and student creativity.